MEKANISME PEMEKARAN WILAYAH TERHADAP CALON KABUPATEN KEPULAUAN SELAUT BESAR NANGGROE ACEH DARUSSALAM (NAD): Irmayadi Sastra - Sastra, Irmayadi (Fakultas Hukum Universitas Islam Jakarta, 2016)
Expansion of Territories is not contradictory to the Constitution of the 1945 Constitution and existing laws and regulations. The formation of the region must meet the technical requirements covering the factors that form the basis of the regional establishment and includes the factors of economic ability, regional potential, defense, security and other factors that enable the implementation of Regional Autonomy. The candidate for Kabupaten Selaut Besar is the new Regency that is separated from the Regency of Induk (Regency of Simeulue) and will run its own governance system and manage all aspects of government in order to take care of its own household. To promote and develop the economic development of the community, it is necessary to prepare human resources that are reliable and potential in their fields to manage natural resources and potential areas in the district. The spirit of expansion or the establishment of the New Autonomous Region is inseparable from the rules and mechanisms contained in Law No. 2 of 2015 on Regional Government and Government Regulation Number 78 of 2007 on Procedures for the Establishment, Elimination and Merger of Regions so that in the acceleration of the division does not violate the law, applicable law. ABSTRAK Pemekaran wilayah tidak bertentangan dengan konstitusi UUD 1945 dan peraturan perundang-undangan yang ada. Pembentukan daerah harus memenuhi persyaratan teknis yang meliputi faktor yang menjadi dasar pembentukan daerah serta mencakup faktor kemampuan ekonomi, potensi daerah, pertahanan, keamanan dan faktor lain yang memungkinkan terselenggaranya Otonomi Daerah. Calon Kabupaten Kepulauan Selaut Besar adalah bakal Kabupaten Baru yang dipisahkan dari Kabupaten Induk (Kabupaten Simeulue) dan akan menjalankan sistem pemerintahan sendiri serta mengatur segala aspek pemerintahan dalam rangka mengurus rumah tangganya sendiri. Untuk memajukan dan mengembangkan pembangunan ekonomi masyarakat maka perlu dipersiapkan sumber daya manusia yang handal dan potensial dibidangnya guna mengelolah sumber daya alam dan potensi daerah yang ada pada Kabupaten tersebut. Semangat pemekaran atau pembentukan Daerah Otonom Baru ini tidak terlepas dari aturan serta mekanisme yang tertuang dalam UU Nomor 2 Tahun 2015 tentang Pemerintah Daerah dan PP Nomor 78 Tahun 2007 tentang Tata Cara Pembentukan, Penghapusan, dan Penggabungan Daerah agar dalam percepatan pemekaran tersebut tidak melanggar undang-undang yang berlaku.